Chemical Composition And Digestibility Of Natural And Domestic Food Of The Lar Gibbon (Hylobates Lar) In Malaysia - Subramaniam, Vellayan (1981)
The collection of samples of natural foods of the lar gibbon (Hylobates lar) was undertaken at the Krau Gare Reserve over a period of on e year. A total of 145 plant items were collected of which 35 were consumed by the lar gibbon. Food saqples were chemically analyzed for both primary and secondary metabolites. The non-eaten food items were analyzed for all or some of these measures. The principal diet of the lar gibbon is Ficus spp. There are probably attracted to these most because of their soft and succulent nature. The protein and amino acid requirements in the wild are achieved by consuming young leaves and invertebrates. The lar tends to avoid foods of high fat content. It avoids mature leaves due to their poor nutritive value. The lar obtains carbohydrates, readily available sugars and energy from the ripe pulp of fruits.High in vivo digestibility values were obtained for the formulated basal diet when compared to the natural and domestic foods. The in vivo and in vitro assays of Randia scortechinii, knema cinerea and Sarcotheca grifithii gave values in fairly good agreement with one another. The present study concludes that the lar gibbon lacks specialisation of the gastro-intestinal tract for either the bulk intake of fibrous food or for the detoxification of alkaloids. The lar gibbon tends to avoid food with a high level of tannins. Therefore they are selective feeders in comparison with some other primates, being restricted to a diet of succulent fruit pulp, young leaves, flowers and invertebrates.